Purchasing power parity and free trade area. - Lee, Chin (The Publisher, 2010)
The aim of this paper is to apply recently developed panel cointegration techniques proposed by Pedroni (1999, 2004) to evaluate the effectiveness of various regional trade agreements by examine the goods market integration between trading partners using purchasing power parity (PPP). The results obtained from panel cointegration tests strongly support the validity of long-run PPP in almost all cases. Evidence of price convergence suggested that the panel countries of free trade areas (FTAs) are integrated, hence FTAs has fostererd the price convergence.